New Approaches for Controlling Saprolegnia parasitica, the Causal Agent of a Devastating Fish Disease - Gregory Earle,; William Hintz, (Tropical Life Sciences Research, 2014)
Pathogenic oomycetes have the ability to infect a wide range of plant and animal hosts and are responsible for a number of economically important diseases. Saprolegniasis, a disease affecting fish eggs and juvenile fish in hatcheries worldwide, is caused by the pathogenic oomycete Saprolegnia parasitica. This disease presents as greyish-white patches of filamentous mycelium on the body or fins of fish and is associated with tissue damage leading to death of the animal. Traditionally, saprolegniasis was controlled using Malachite green; however, this chemical was banned in 2002 due to its carcinogenic and toxicological effects. As a direct result of this ban, there has been a recent resurgence of saprolegniasis in the aquaculture industry, leading to economic losses world-wide. Hence, there is an urgent need to find alternative methods to control this pathogen. We discuss the use of molecular approaches for the study of saprolegniasis, which are anticipated to enable the development of effective fish vaccines and the potential for the development of new methods to control this devastating disease. Oomycetes patogenik mempunyai keupayaan untuk menjangkiti banyak tumbuhan dan haiwan perumah. Saprolegniasis merupakan penyakit yang memberi kesan terhadap telur ikan dan ikan juvenil di pusat penetasan seluruh dunia, dan berpunca daripada oomycete patogenik Saprolegnia parasitica. Penyakit ini menunjukkan miselium berfilamen bertompok kelabu-putih di atas badan atau sirip ikan dan berkaitan dengan kerosakan tisu yang membawa kepada kematian haiwan tersebut. Dahulunya, saprolegniasis dikawal menggunakan Malachite green; namun demikian bahan kimia ini diharamkan pada tahun 2002 kerana kesan-kesan karsinogenik dan toksikologi. Akibat daripada ini, kebelakangan ini terdapat peningkatan saprolegniasis di industri akuakultur, yang membawa kepada kerugian ekonomik seluruh dunia. Maka, ada keperluan segera untuk mencari kaedah alternatif bagi mengawal patogen ini. Kami akan membincangkan penggunaan pendekatan molekular dalam kajian saprolegniasis, yang dijangka membolehkan perkembangan vaksin ikan yang berkesan dan potensi perkembangan kaedah baru untuk mengawal penyakit ini.